2011
DOI: 10.1007/s00442-011-2000-6
|View full text |Cite
|
Sign up to set email alerts
|

Species replacement by a nonnative salmonid alters ecosystem function by reducing prey subsidies that support riparian spiders

Abstract: Replacement of a native species by a nonnative can have strong effects on ecosystem function, such as altering nutrient cycling or disturbance frequency. Replacements may cause shifts in ecosystem function because nonnatives establish at different biomass, or because they differ from native species in traits like foraging behavior. However, no studies have compared effects of wholesale replacement of a native by a nonnative species on subsidies that support consumers in adjacent habitats, nor quantified the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 52 publications
4
75
0
Order By: Relevance
“…These findings have important management implications because changes in the functioning of fish assemblages can potentially alter the structure and function of entire aquatic communities (Benjamin et al, 2011). Our GCA analyses show terrestrial invertebrates to be a relatively important prey source for trout, potentially offsetting predation pressure on aquatic invertebrates in the streams where they have replaced redfin and the other small-bodied native species.…”
Section: Discussionmentioning
confidence: 77%
“…These findings have important management implications because changes in the functioning of fish assemblages can potentially alter the structure and function of entire aquatic communities (Benjamin et al, 2011). Our GCA analyses show terrestrial invertebrates to be a relatively important prey source for trout, potentially offsetting predation pressure on aquatic invertebrates in the streams where they have replaced redfin and the other small-bodied native species.…”
Section: Discussionmentioning
confidence: 77%
“…Spiders -Spiders living in riparian zones receive a large proportion of food resources from freshwaters in the form of emerging aquatic insect subsidies [58][59][60]. Briers et al (2005) found that over 40% of the diet of riparian spiders comprised of adult aquatic insects, but this decreased to less than 1% at 20 m from the stream [61].…”
Section: Impacts Of Aquatic Resource Subsidies On Specific Terrestriamentioning
confidence: 99%
“…If there is a disruption in the flow of allochthonous resources due to landscape degradation, not only will the consumer be impacted, but the entire trophic system has the potential to be altered. The impacts of invasive species can propagate to adjacent ecosystems, for instance, the invasive brook trout reduced emergence rates of aquatic insects by 24%, which caused 6-20 % fewer spiders in the riparian zone, and therefore, altered ecosystem function in stream-riparian food webs [59].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…If they consume similar types and amounts of prey to the native predators, then impacts on lower trophic levels may be minimal. On the other hand, if prey selectivity or consumption rates differ from the native predator(s), then it is likely that prey assemblages will be altered, with potential indirect effects on lower trophic levels (Benjamin et al, 2011;Lepori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%